ANALISIS IMPLEMENTASI PARADIGMA INTEGRASI ILMU PENGETAHUAN DI PERGURUAN TINGGI KEAGAMAAN ISLAM: (Kajian Terhadap Karya Akademik Mahasiswa di UIN Walisongo) - Machrus; Yusriyah; Mohamad Sobirin; Mishbah Khoiruddin Zuhri (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2019)
The change from the State Islamic Institute (IAIN) Walisongo to the State Islamic University (UIN) Walisongo has influenced the scientific paradigm. The scientific fields taught and developed by UIN Walisongo are increasingly diverse so that a new paradigm is needed, which is reflected in the vision of UIN Walisongo, namely ‘Leading Islamic Research University Based on the Unity of Science for Humanity and Civilisation in 2038’. The consequence of the vision requires all stakeholders at UIN Walisongo to be involved in realising it, so the understanding of UIN Walisongo's vision must be lived by the entire academic community, including students. This study aims to determine the extent to which students of UIN Walisongo understand the vision of UIN Walisongo. This research is a qualitative research with an interview and field study approach. The results of this study indicate that students of UIN Walisongo understand the vision with the following details: 60% of students use the strategy of local wisdom, 30% of students use the strategy of humanisation of Islamic sciences, and 10% of students use the strategy of spiritualisation of general sciences.